The The Influence of Media and Hydration Time Treatment in Dairy’s Urine Liquid to the Growth of Rosa Hibryda’s Cuttings: The Influence of Media and Hydration Time Treatment in Dairy’s Urine Liquid to the Growth of Rosa Hibryda’s Cuttings - Sugiarto; Muslikah, Siti; Qurania, Anita (Universitas Islam Malang, 2024)
Roses have been known as important horticultural industrial commodity. This research was aimed to know the ideal mixture of media and the effective hydration time of rose cuttings in dairy’s urine liquid. This research was conducted in experimental field of Agricultural faculty of UNISMA, using a plastic house. Randomized Complete Design with two factors was used in this experiment and each treatment was replicated three times. The first factor comprised four levels of medias treatment (soil; soil and rice husk; soil and compost; soil+rice husk+compost). The second factor comprised of three levels of hydration time (3 hours, 6 hours,and 9 hours). The result of this research indicated that the combination of soil media and nine hours hydration of cuttings in dairy’s urine give the highest total buds, compared with the other treatments . Six hours hydration treatment gave the best result in cell enlargement and cell division of the buds compared with the other treatments. The combination of soil, rice husk and compost with six hours hydration treatment of dairy’s urine liquid gave the highest total leaves , fresh root, dry root weight, total fresh weight of cuttings and also its total dry weight.